2002
DOI: 10.1067/mva.2002.121050
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of endovascular abdominal aortic aneurysm repair in patients with conditions considered unfit for an open procedure: A report on the EUROSTAR experience

Abstract: Early and late mortality rates were increased in patients with the preoperative clinical diagnosis "unfit for open surgery and general anesthesia" as compared with patients at "normal" operative risk. EAR appeared of potential benefit in patients with unfit conditions, regardless of the aneurysm diameter. The life expectancy of patients at high risk who are considered for EAR should be longer than 1 year before any realistic gain in life span can be anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 36 publications
1
99
0
3
Order By: Relevance
“…[9] Bu anlamda yapılan en geniş kapsamlı çalışma iki tane karşılaştırma metaanalizinden ortak sonuç olarak yayınlanmış EUROSTAR olup sonuçları; ameliyat esnasındaki kan kaybı, hastanede ve yoğun bakımda kalış süresi, total komplikasyon oranı ve ilk 30 gün içerisinde olan mortalite endovasküler girişimde daha az olarak tespit edilmiş, iki yıllık sağkalım açı-sından iki grup arasında fark tespit edilememiştir. [10,11] Tek merkezli prospektif randomize başka bir merkezin çalışmasında hastaların erken dönem (30 gün) mortaliteleri karşılaştırılmış, EVAR uygulanan olgularda mortalite %1.6 iken, konvansiyonel cerrahi uygulananlarda bu oran %4.6 olarak tespit edilmiştir. [12] Bu olgularda uzun dönem mortalite oranlarına bakıldığında hastalar üç yıl boyunca takip edilmiş, anevrizmaya bağlı ölüm oranı EVAR'da %1, konvansiyonel cerrahide ise %6 olarak tespit edilmiş ve bu sonuç istatistiksel olarak anlamlı bulunmamıştır (p=0.06).…”
Section: İstatistiksel Analizlerunclassified
“…[9] Bu anlamda yapılan en geniş kapsamlı çalışma iki tane karşılaştırma metaanalizinden ortak sonuç olarak yayınlanmış EUROSTAR olup sonuçları; ameliyat esnasındaki kan kaybı, hastanede ve yoğun bakımda kalış süresi, total komplikasyon oranı ve ilk 30 gün içerisinde olan mortalite endovasküler girişimde daha az olarak tespit edilmiş, iki yıllık sağkalım açı-sından iki grup arasında fark tespit edilememiştir. [10,11] Tek merkezli prospektif randomize başka bir merkezin çalışmasında hastaların erken dönem (30 gün) mortaliteleri karşılaştırılmış, EVAR uygulanan olgularda mortalite %1.6 iken, konvansiyonel cerrahi uygulananlarda bu oran %4.6 olarak tespit edilmiştir. [12] Bu olgularda uzun dönem mortalite oranlarına bakıldığında hastalar üç yıl boyunca takip edilmiş, anevrizmaya bağlı ölüm oranı EVAR'da %1, konvansiyonel cerrahide ise %6 olarak tespit edilmiş ve bu sonuç istatistiksel olarak anlamlı bulunmamıştır (p=0.06).…”
Section: İstatistiksel Analizlerunclassified
“…The large deposit of multicenter, prospectively collected data on the European EVAR experience also provides a great source for analyses: the EUROSTAR (EUROpean collaborators on Stentgraft Techniques for abdominal aortic Aneurysm Repair) Registry (4392 patients, 1996 to 2002). [17][18][19][20] In the present review, we will address EVAR indications, contraindications, devices, outcomes, complications, en-dograft surveillance, and future directions. This is an exciting time for the management of AAAs, because there are many more options for high-risk patients.…”
Section: Endovascular Repair Of Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…273 In addition, the EVAR trial 1 274 and DREAM (Dutch Randomized Endovascular Aneurysm Management) trial 275 demonstrated favorable results of EVAR in the initial and intermediate phases.…”
Section: Results Of Evar (1) Results In the Initial And Intermediate mentioning
confidence: 99%